Determining the optimum gamma irradiation dose for developing novel maize genotypes. Issue 4 (4th July 2021) - Matova, Prince M.; Kamutando, Casper N.; Sarsu, Fatma; Magorokosho, Cosmos; Labuschagne, Maryke
ABSTRACT: Mutation breeding has been used successfully worldwide to generate crop varieties with various traits, including pest resistance. Before any mutation breeding is initiated, radio-sensitivity tests need to be conducted to determine optimum doses for mutagenesis. In this study, radio-sensitivity tests were conducted on three maize ( Zea mays L.) genotypes with six gamma irradiation doses. Highly significant effects of mutagenesis on days to seedling emergence, emergence percentage, and seedling height were observed. Regressing seedling height on gamma-ray doses estimated the lethal dose 50 for the three varieties. The study showed that maize seeds were responsive to gamma irradiation and optimal doses can be used to generate novel genetic variability for effective breeding. Doses with high relative biological effectiveness for mutation breeding ranged from 160 gy – 275 gy.